Nanomaterials for medical applications - Aguilar, Zoraida P. (Elsevier, 2012)
This title covers recent advances in a variety of biomedical applications of nanostructured materials, as the field evolves from prototype device to real-world application. It presents the main types of nanomaterial used in medical application today: semiconductor nanomaterials, magnetic nanomaterials, metal nanoparticles, carbon nanomaterials, hydrogel nanocomposites, liposomes, dendrimers, polymer nanocomposites, and biodegradable polymers. Structurally the work is demarcated into the six most popular areas of research: (1) biocompatibility of nanomaterials with living organisms in their various manifestations; (2) nanobiosensors for clinical diagnostics, detecting biomolecules which are useful in the clinical diagnosis of genetic, metabolically acquired, induced or infectious disease; (3) targeted drug delivery for nanomaterials in their various modifications; (4) nanomedical devices and structures which are used in the development of implantable medical devices and structures such as nanorobots; (5) nanopharmacology, as novel nanoparticles are increasingly engineered to diagnose conditions and recognize pathogens, identify ideal pharmaceutical agents to treat the condition or pathogens, fuel high-yield production of matched pharmaceuticals (potentially in vivo), locate, attach or enter target tissue, structures or pathogens; and dispense the ideal mass of matched biological compound to the target regions; and (6) nanotoxicology and remediation, which focuses on finished and on-going various toxicity evaluations on various nanomaterials that are used and currently being developed for medical applications.